Factors Associated with the Incidence of Gastritis in Patients at Faisal Islamic Hospital Makassar - K, Hairuddin; Yulis, Dian Meiliani; Sahalessy, Yona; Tomasoa, Johanna; Rumaseb, Ester; Said, Asbath; B, Sari Arie Lestari (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Gastritis is known in the community as heartburn or heartburn. It is an inflammation of the mucosal wall. It can occur suddenly and is usually characterized by nausea and vomiting, pain, bleeding, weakness, decreased appetite, or headache. It can be caused by habitual consumption of sensitive foods, or often by a frivolous diet. The individual overeats, eats foods that are overly seasoned or contain microorganisms. Other causes of gastritis include alcohol, smoking, age, aspirin, bile reflux or radiation therapy. The purpose of this study was to determine the factors associated with the incidence of gastritis in patients at Faisal Makassar Islamic Hospital and to determine the relationship between the patient's diet and smoking history with the incidence of gastritis in patients. This study is a type of retrospective Exposfacto research with the design / design of Crossectional Study, by obtaining primary data (data obtained directly from patients) and secondary data (data obtained from the medica record of Faisal Makassar Islamic Hospital and obtained from family or people closest to the patient). The population in this study were all patients suffering from gastrointestinal diseases at Faisal Islamic Hospital Makassar. The sample in this study were all patients suffering from gastritis disease at Faisal Islamic Hospital Makassar. Chi-Square test P value = 0.003 < α = 0.05. This means that a person's irregular diet is very influential on the occurrence of gastritis. the results of bivariate analysis showed that there was no relationship between smoking history and the incidence of gastritis at Faisal Islamic Hospital Makassar with Chi-Square test P=0.117 and < α = 0.05.